Senior Management Degree of Crisis Management Practice and the Ability to Make Decisions to Solve University Problems at Mu'tah University in Karak - Al Mallahim, Wafa Salem (Journal of Economic, Administrative and Legal Sciences, 2019)
The study aimed at measuring senior management degree of crisis management practice and the ability to make decisions to solve university problems at Mu'tah University in Karak Governorate in Jordan. The researcher used the descriptive analytical and survey method. Then she developed two scales; First: to measure crisis management, and second: to measure making decisions by senior management to solve university problems. The sample of the study consisted of (85) senior management administrators (males &females) at the University of Karak.The results revealed that the total mean of the crisis management came high with a mean of (3.71) and a percentage of (74.2%), where the crisis planning was high with a percentage of (80.4%). The communication process in crises was high at (77%), And facing the crises by (71.2%), while the crisis teams came in a medium degree with (68.2%). The results showed that the total mean of the decision-making was medium with a mean of (3.50) and a percentage of (70%), while decision making and identifying the problem came in the first rank with the highest mean of (3.85), and a percentage of (77%), while decision making and collecting data came medium with a (72.8%). But decision making and choosing the alternative came medium with (69.4%), while decision making came medium and ranked last with a percentage of 60.6%.The results also indicated that there were no statistically significant differences due to the effect of gender, with a value of (0.325) and a significance of (0.570). And there were a statistically significant differences due to the administrative experience, where the differences came in favor of (20 years and more) group. The result revealed a positive significant relationship between the level of senior management of crisis management practice to solve university problems at Mu'tah University and the level of senior management ability to make decisions to solve university problems.
Keywords: senior management; crisis management; decision-making; Mutah University